Controlling Microsized Polymorphic Architectures with Distinct Linear and Nonlinear Optical Properties. Issue 7 (27th March 2015) - Xu, Jialiang; Semin, Sergey; Cremers, Jonathan; Wang, Linjun; Savoini, Matteo; Fron, Eduard; Coutino, Eduardo; Chervy, Thibault; Wang, Chunliang; Li, Yongjun; Liu, Huibiao; Li, Yuliang; et al.
<x xml:space="preserve">Abstract</x> Controlled assembly of polymorphic organic materials into well‐defined microstructures with specific properties is desirable for next‐generation optoelectronic devices. Here, a multistep drop‐casting technique is developed for the selective fabrication of kinetically and thermodynamically stable polymorphic microfibers and microplates with tunable optical responses in the linear and nonlinear optical regimes.